Muslim Religiosity, Attitude, and Parental Influence On Students’ Intention Not to Perform Academic Dishonesty: A Study of Accounting Students in Malaysian Islamic-Focused Universities - Nor Azah Abdul Jalil; Dato' Hasnah Hj Haron; Nurul Nazlia Jamil; Nathasa Mazna Ramli (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025